Bariatric Surgery, Polycystic Ovary Syndrome, and Infertility - James Butterworth; Jean Deguara; Cynthia-Michelle Borg (Hindawi Limited, 2016)
Background. Polycystic ovary syndrome (PCOS) is the commonest cause of female infertility. Visceral obesity and insulin resistance are key pathophysiological mechanisms behind PCOS. Women suffering from this syndrome and infertility often seek bariatric surgery hoping that they would be able to conceive postoperatively. Objective. At present, there is no consensus on the role of bariatric surgery in the management of PCOS-associated infertility within the medical community, making it difficult to give specific advice to these women, so a review of the literature was necessary. Results. A detailed review of the literature was performed. Only 6 manuscripts were relevant and contained quantitative data. They demonstrated that bariatric surgery results in postoperative conception rates varying from 33% to 100%. Surgery is also associated with amelioration of menstrual irregularities, hormonal abnormalities, and hirsutism that are associated with PCOS. These studies were retrospective and only had a small number of participants with infertility. Conclusions. Bariatric surgery has been shown to conclusively improve life expectancy, quality of life, and comorbidities like type 2 diabetes and obstructive sleep apnea. However, further research is required to identify whether weight loss surgery results in significant improvement in fertility of women with PCOS and to investigate which operation has the best results.